Relationship between facial asymmetry and positional plagiocephaly analyzed by three-dimensional computed tomography. Issue 3 (March 2020) - Sasaki, Jun; Hasegawa, Shogo; Yamamoto, Satoshi; Watanabe, Satoshi; Miyachi, Hitoshi; Nagao, Toru
Abstract: Purpose: A relationship between positional cranial deformation and facial asymmetry has been suggested; however, details regarding this relationship remain to be clarified. This study aimed to elucidate the relationship between facial asymmetry and positional plagiocephaly using three-dimensional computed tomography (3D-CT). Methods: One-hundred-and-twenty-nine patients were included, and cranial vault asymmetry index (CVAI) and cephalic index (CI) were used as indicators of positional cranial deformation. Temporal muscle was constructed using 3D-CT data, and its volume was measured. VRL, Me (vertical reference line (VRL)-anterior nasal spine (ANS) and menton (Me) line) angle and the frontal occlusal plane (FOP) angle were measured. Results: CVAI and VRL, Me angle (R2 = 0.31, P < 0.0001), VRL, Me angle and temporal muscle volume (R2 = 0.13, P < 0.0001), and FOP angle and VRL, Me angle were significantly correlated (R2 = 0.32, P < 0.0001), but CVAI and FOP angle were not (R2 = 0.08). Multiple linear regression analysis indicated that CVAI, FOP angle, and variable temporal muscle volume were significant predictors of VRL, Me angle [(F (5, 123) = 14.94, P < .0001, R2 = 0.38)]. Conclusions: Our results revealed that mandibular deviation was associated with contralateral head slant and ipsilateral increase in temporal muscle volume. Positional plagiocephaly may be a cause of facial asymmetry, and such deviations may occur in the temporal muscle.